Tinjauan tentang Kebebasan Mengeluarkan Pendapat Syaykh Al-Zaytun Menurut Siyasah Dusturiyah dan Pasal 28 E Undang-Undang Dasar 1945 - Fath, Imam Nur Sidiq Al; Sajali, Munawir; Rohmah, Siti Ngainnur (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Indonesia is a pluralistic country with diverse religions, races, ethnicities, and customs, making freedom of expression an essential right protected by law. Article 28E of the 1945 Constitution guarantees every citizen the right to freely express their beliefs and opinions. From the perspective of fiqh Siyasah Dusturiyah (Islamic constitutional politics), freedom of expression is a right that must be safeguarded by the state as long as it aligns with the principles of deliberation and does not contradict Islamic law. This study aims to examine the freedom of expression of Syaykh Al-Zaytun in light of Siyasah Dusturiyah and Article 28E of the 1945 Constitution. The research uses a normative juridical approach with primary data sources including the Constitution and the book Ilmu Hukum dalam Simpul Siyasah Dusturiyah by Ali Akhbar Abaib Mas Rabbani Lubis, as well as secondary sources such as books, journals, documents, and legal regulations. The findings indicate that Syaykh Al-Zaytun’s freedom of expression is permissible under both perspectives, provided certain conditions are met: it must comply with Islamic law and national law, uphold public interest, cause no harm, and be accompanied by social responsibility. Syaykh Panji Gumilang’s views should be understood as part of public discourse, not hate speech, as they aim to foster nationalism and the common good.